Pengaruh Media I Spring Suite 11 Terhadap Hasil Belajar Membaca Bahasa Indonesia Kelas IV SD Inpres Kampung Parang Kab. Gowa - Wahidin Syarif; Tasrif Akib; Basse Syukroni Baso (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to determine the effect of ISPRING Suite 11 media on the learning outcomes of reading Indonesian for class IV at SD INPRES KAMPUNG PARANG REGENCY. GOWA. This type of research is One-Group Pretest-Posttest Design research. The sample used was 21 grade IV students at SD Inpres Kampung Parang. The instrument used to collect data is an essay. The results of this research show that the data was analyzed using descriptive analysis and inferential analysis. Data were analyzed using descriptive statistical analysis techniques. It was found that the average (mean) pretest value was 62.38 while the average (mean) posttest was 74.52, the average value on the posttest was higher than the average value on the pretest. In hypothesis testing using the independent sample t-test, where the data tested is hypothesis testing carried out on the pretest and posttest results. Based on the management of the hypothesis results, Sig (2.Tailed) = 0.000, meaning that H0 is rejected because Sig (2.Tailed) ) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.405 > 0.05). In the T test analysis, Sig < ttable or (0.405 < 1.684). Testing this hypothesis, it can be concluded that there is an influence on the use of I Spring Suite 11 media on the results of learning to read Indonesian for class IV at SD Inpres, Kampung Parang, Gowa Regency.